Conformal Pressure and Fast-Charging Li-Ion Batteries. Issue 4 (1st April 2022) - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P.; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew N.; Kasse, Robert M.; Thampy, Vivek; Yusuf, Maha; Weker, Johanna Nelson; Shyam, Badri; Subbaraman, Ram; et al.
Abstract : Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5 Mn0.3 Co0.2 O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10–125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogeneous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.